EMPAT PILAR PENDIDIKAN UNESCO DI PAUD TERPADU MUTIARA YOGYAKARTA - Handayani, Iys Nur (AlBanna: Jurnal Pendidikan Islam Anak Usia Dini, 2023)
This study aims to determine the application of the four pillars of UNESCO education in PAUD Terpadu Mutiara Yogyakarta. The method used in this research is descriptive which gives a complete picture. This study uses interview and documentation techniques to collect data, then the data is analyzed and described with an inductive-deductive thinking pattern. This study obtained the results of the implementation of the four pillars of UNESCO education at PAUD Terpadu Mutiara Yogyakarta, as follows: (1) Learning to know (learning to know) by applying an Islamic approach; (2) Learning to be (learning to be something) by applying child-centered learning and learning by doing (learning by doing) carried out by students; (3) Learning to be (learning to be something) by habituation (habbit forming) in the school environment; (4) Learning to live together (learning to live together) through the example (uswatun hasanah) given by the teacher. The four pillars of UNESCO are interrelated with each other, so that they are carried out in a sustainable manner. In the end, the achievement of the implementation of the four pillars of UNESCO education in PAUD Terpadu Mutiara Yogyakarta can be realized. This research aims to determine the implementation of the four pillars of UNESCO education in PAUD Terpadu Mutiara Yogyakarta. The method used in this research is descriptive which gives a complete picture. This study uses interview and documentation techniques to collect data, then the data is analyzed and described with an inductive-deductive thinking pattern. This study obtained the results of the implementation of the four pillars of UNESCO education at PAUD Terpadu Mutiara Yogyakarta, as follows: (1) Learning to know (learning to know) by applying an Islamic approach; (2) Learning to be (learning to be something) by applying child-centered learning and learning by doing (learning by doing) carried out by students; (3) Learning to be (learning to be something) by habituation (habbit forming) in the school environment; (4) Learning to live together (learning to live together) through the example (uswatun hasanah) given by the teacher. The four pillars of UNESCO are interrelated with each other, so that they are carried out in a sustainable manner. In the end, the achievement of the implementation of the four pillars of UNESCO's education at PAUD Terpadu Mutiara Yogyakarta was realized to the maximum.